(untitled) (Eurasian Journal of Ecology, 2018)
The paper presents the results of electron microscopy of strains of equine influenza virus, isolated from 2010 to 2012. when conducting monitoring activities. Expeditions to the South Kazakhstan, Zhambyl, Almaty, East Kazakhstan, Kostanay, Aktyubinsk and West Kazakhstan oblasts were conducted to carry out epizootological monitoring of equine influenza in the Republic of Kazakhstan. In total, for the years 2010-2012. For laboratory investigations in different regions of the Republic of Kazakhstan, 2404 samples were collected and delivered to NIIIBB . Based on the results of the studies, the main morphometric properties were determined. Electron microscopic analysis showed no contamination by foreign microorganisms in purified preparations of the horse flu virus. During the purification process, the virions retain their structure. Strains A / equine / Baizak / 09/2012, A / equine / Kostanai / 09/2012, A / equine / Matybulak / 10/2012 and A / equine / LKZ / 09/2012 equine influenza virus in the populations of the studied isolates have mainly round and oval shapes. The size of round virions is 70 – 200 nm in diameter, and the length of oval ones is of the order of 100 -300 nm. About 72% of the population of equine influenza isolates are virions with a diameter of 110 – 180 nm. The surface of the viral particles is covered with spines of 6-8 nm in height, and the thickness of the outer shell is 8.5-9 nm. In all studied isolates of the equine influenza virus, the majority of the virions are round (95%) and oval (5%) virions. For all isolates polymorphism is not typical. The conducted studies showed that the investigated isolates practically do not differ both in morphology and in such physical parameters as the floating density and the sedimentation constant of the virion. All indices lie in the range of values characteristic for the family of orthomixoviruses. However, in view of the development of genetically mutation among the population of the equine influenza virus, A / equine / LKZ / 09/2012, rounded viruses with a size of about 450 nm were found and filamentary lengths over 750 nm. These virions are characterized by the preservation of the surface structure of glycoproteins, but an initial degree of disintegration of the virus for the subsequent release of ribonucleoprotein (RNP) is observed. Key words: virus, equine influenza, ultracentrifugation, electron microscopy, physical constants.